Histopathology of Post Kala-azar Dermal Leishmaniasis - Ramesh, V (Indian J Dermatol, 2020)
The various lesions seen in the clinical presentation of post kala-azar dermal leishmaniasis (PKDL) are reflected in the histopathology of the type of lesion biopsied. The cells that form the dermal infiltrate include lymphocytes, histiocytes, and plasma cells in varying proportions. The infiltrate, which is mild and confined to the superficial dermis in macular lesion becomes denser with the increasing severity of the lesion. Leishman–Donovan bodies (LDB) in general are rarely demonstrable in macules and somewhat infrequently in the rest, though at times they may be numerous; mucosal lesions offer a greater chance of visualizing LDB than biopsies from the skin. A characteristic histomorphology in nodules is prominent follicular plugging with a dense plasma cell-rich lymphohistiocytic dermal infiltrate that shows an abrupt cut-off in the lower dermis, an appearance highly suggestive of PKDL even in the absence of LDB. Russell bodies within plasma cells, vascular changes, and xanthoma-like hue have been seen in plaques from chronic PKDL. The histopathologic picture in some may also mimic that seen in tuberculoid and lepromatous leprosy, and other granulomatous dermatoses. In contrast to Indian PKDL, epithelioid cell granulomas with giant cells are more common in African PKDL, and vascular changes are rare though neuritis showing LDB has been described.